2023
DOI: 10.1002/dad2.12409
|View full text |Cite
|
Sign up to set email alerts
|

Plasma amyloid beta 40/42, phosphorylated tau 181, and neurofilament light are associated with cognitive impairment and neuropathological changes among World Trade Center responders: A prospective cohort study of exposures and cognitive aging at midlife

Abstract: Introduction: World Trade Center (WTC) responders are experiencing a high risk of mild cognitive impairment (MCI) and dementia, though the etiology remains inadequately characterized. This study investigated whether WTC exposures and chronic post-traumatic stress disorder (PTSD) were correlated with plasma biomarkers characteristic of Alzheimer's disease (AD) neuropathology. Methods: Eligible participants included WTC-exposed individuals with a baseline cognitive assessment and available plasma sample. We exam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 51 publications
0
5
0
Order By: Relevance
“…These results have been replicated in serological studies of humans, which report that cognitively impaired WTC responders have an upregulated macrophagic reaction in pathways indicating neuroimmunologic response, while neuroimaging studies have found evidence of glial activation and hippocampal inflammation in heavily exposed responders . Seeking potential linkages between neuroinflammation and cognitive outcomes, prior work suggests a potential role for phosphorylated tau and accompanying neurodegeneration . Further work identifying a mechanism for this process may provide useful treatment targets for WTC responders and other persons with inhaled neurotoxicants.…”
Section: Discussionmentioning
confidence: 76%
See 2 more Smart Citations
“…These results have been replicated in serological studies of humans, which report that cognitively impaired WTC responders have an upregulated macrophagic reaction in pathways indicating neuroimmunologic response, while neuroimaging studies have found evidence of glial activation and hippocampal inflammation in heavily exposed responders . Seeking potential linkages between neuroinflammation and cognitive outcomes, prior work suggests a potential role for phosphorylated tau and accompanying neurodegeneration . Further work identifying a mechanism for this process may provide useful treatment targets for WTC responders and other persons with inhaled neurotoxicants.…”
Section: Discussionmentioning
confidence: 76%
“… 32 , 33 Seeking potential linkages between neuroinflammation and cognitive outcomes, prior work suggests a potential role for phosphorylated tau and accompanying neurodegeneration. 34 Further work identifying a mechanism for this process may provide useful treatment targets for WTC responders and other persons with inhaled neurotoxicants.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Neurofilament light (NfL), a marker of neural axonal damage, was found to be elevated in patients with a history of PTSD and mild TBI in a single study [77]. However, two other studies did not observe a significant association between PTSD and NfL levels [61,79].…”
Section: Biochemical Marker Studiesmentioning
confidence: 98%
“…Neurofilament light (NfL), a marker of neural axonal damage, was found to be elevated in patients with a history of PTSD and mild TBI in a single study [66]. However, two other studies did not observe a significant association between PTSD and NfL levels [50,68].…”
Section: Biochemical Marker Studiesmentioning
confidence: 98%